PENGARUH RETURN ON ASSET (ROA), RETURN ON EQUITY (ROE), DAN NON-FERFORMING FINANCING (NPF) TERHADAP CAPITAL ADEQUACY RATIO (CAR) PADA BANK UMUM SYARIAH PERIODE 2020 – 2024 - ENDE; Deshinta Maya; Didin Rasyidin Wahyu (LPPM STIE Mujahidin Tolitoli, 2025)
This study analyzes the effect of Return on Assets (ROA), Return on Equity (ROE), and Non-Performing Financing (NPF) on the Capital Adequacy Ratio (CAR) of seven Islamic Commercial Banks in Indonesia for the period 2020–2024 using a quantitative multiple linear regression method, which found that ROA has a significant positive effect, ROE and NPF have a negative but insignificant effect, and simultaneously, all three have a significant effect with a contribution of 32.3%, which empirically confirms the importance of asset-based profitability in strengthening capital adequacy. However, this study is limited to three variables, a period affected by the pandemic, and a limited sample size, so the results need to be interpreted with caution.